Optimizing the exercise prescription for depression: the search for biomarkers of response. (August 2015) - Medina, Johnna L; Jacquart, Jolene; Smits, Jasper AJ
Highlights: Exercise has shown effects for depression that rival those of other established interventions. Exercise can target several neuroinflammatory mediators of depression pathology. Exercise may be effective in increasing BDNF production in genetically at-risk groups. Exercise may help correct an inflammatory imbalance among depressed individuals. Abstract : There is growing support for the efficacy of exercise interventions for the treatment of individuals who present with mild-to-moderate depression. The variability in treatment response across studies and individuals suggests that the efficacy of exercise for depression will be most optimal when prescribed to individuals who are most prone to respond. The present article reviews contemporary theoretical accounts and recent empirical data pointing to neuroinflammatory states and neurotrophin production as possible biomarkers of the antidepressant response to exercise. The larger exercise and depression literatures provide justification for elevated levels of pro-inflammatory cytokines and deficits in BDNF production as putative matching variables. Although there is some empirical support for these hypotheses, it is clear that this research warrants replication and extension. We offer a few suggestions for future research in this emerging area.